Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

kde123

  • 3 years ago

solve: 78=-2(m+3)+m

  • This Question is Closed
  1. AbhimanyuPudi
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    78= -2m-6+m 78= -m-6 78+6= -m 84= -m m= -84

  2. AbhimanyuPudi
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Just rearrange the like terms in this type of problems...

  3. andriod09
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    \[78=-2(m+3)+m\]\[78=-2m-6+m\]\[84=-m\]\[m=-84\]

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy